2019
DOI: 10.29252/ijree.4.2.29
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Efficacy of Experience-Based Learning (EBL) Strategies for Improving the Speaking Fluency of Upper-intermediate Male and Female Iranian EFL Students

Abstract: Learning from experience is a central physiological and theoretical idea in adult language learning which has become increasingly important in the field of second language acquisition (SLA) and is closely connected to task-based language teaching (TBLT). Accordingly, this study was designed to investigate the role of experience-based learning strategies in developing male and female upper-intermediate EFL learners' speaking fluency. To this end, from the target population of 300 language learners attending eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…As noted, the impacts of cooperative learning on learners' speaking skills and frames of mind have been frequently shown and affirmed by studies led in L1 and L2 learning situations (e.g. Namaziandost, Nasri, & Rahimi Esfahani, 2019;Ning, 2011;Talebi & Sobhani, 2012;Pattanpichet, 2011;Sühendan & Bengü, 2014). However, studies in this area with EFL students in Iran are rare.…”
Section: The Impact Of Cooperative Learning On Developing Speaking Abmentioning
confidence: 80%
See 2 more Smart Citations
“…As noted, the impacts of cooperative learning on learners' speaking skills and frames of mind have been frequently shown and affirmed by studies led in L1 and L2 learning situations (e.g. Namaziandost, Nasri, & Rahimi Esfahani, 2019;Ning, 2011;Talebi & Sobhani, 2012;Pattanpichet, 2011;Sühendan & Bengü, 2014). However, studies in this area with EFL students in Iran are rare.…”
Section: The Impact Of Cooperative Learning On Developing Speaking Abmentioning
confidence: 80%
“…A huge number of studies indicated that the utilization of cooperative learning techniques can result in positive attitudes towards cooperative learning and increased speaking skills (Alharby, 2015;Nasri & Biria, 2017;Suhendan & Bengu, 2014). Cooperative learning methods, which vary from traditional learning methods, have a few advantages resulting from social cooperation between students (Leong & Ahmadi, 2017;Namaziandost, Nasri, & Rahimi Esfahani, 2019). Classroom social interactions, according to Mackey (2007), are effective for overall language progress.…”
Section: The Impact Of Cooperative Learning On Developing Speaking Abmentioning
confidence: 99%
See 1 more Smart Citation
“…Reading extensively is an individual activity which is based on the learners' interest (Nation, 1997). ER enhances reader's reading skills and it is easy to teach EFL learners to read better through ER which is enjoyable to them (Hosseini, Nasri, & Afghari, 2017;Namaziandost, Nasri, & Rahimi Esfahani, 2019;Nuttal, 2000). The fundamental objective of an ER program is to provide a situation for learners to enjoy reading a foreign language and unfamiliar authentic texts silently at their own pace and with sufficient understanding (Day & Bamford, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The passage which consists of more than one sentence is considered as a text. Therefore, specified linguistic features presented in that passage can be recognized as contributing to its whole unity and giving it texture (Namaziandost, Nasri & Rahimi Esfahani, 2019).…”
mentioning
confidence: 99%